Pemeliharaan Tanaman Obat Keluarga (TOGA) dalam Upaya Meningkatkan Kesehatan Masyarakat di Desa Mata Wawatu - Ardinawati Ardinawati; Asnita Sari; Dwi Febriani; Evitri Anggraeni; Fadilla Aulia Savana; La Ode Rifaldy Rizqi Ramadan.M; Miftahul Hasanah; Mila Angraeni; Muhammad Arifin; Rifdah Molidah; Rizda Sandiva Saputri; Rossa Aprilia Wulan As’ad; Wa Ode Yanti; Zahra Nuril Anwar; Zahratul Jannah; Devi Savitri Effendy; Ramadhan Tosepu; Nurmaladewi Nurmaladewi; Suhadi Suhadi (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
This article discusses the maintenance of Family Medicinal Plants (TOGA) in Mata Wawatu Village as an effort to improve public health. The aim of this program is to provide information to the public regarding the benefits and cultivation techniques of medicinal plants. The methods employed include qualitative research with a descriptive approach, encompassing observations, interviews, and documentation collection. The findings of this study indicate that this initiative has successfully enhanced the community's understanding of TOGA and encouraged them to utilize medicinal plants in their daily lives. This program is expected to improve the health and well-being of the community and reduce dependence on chemical medications